Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper analyzes Spain's sustainable growth rate. It sheds some light on Spain's medium-term growth prospects by looking into the key factors driving potential growth, both in the past and likely in the future, and international experience of countries in the aftermath of financial crisis. The paper suggests Spain is likely to face a long period of moderate growth (about 1 1\2 -2 percent) and high unemployment, but policy action-especially that directed toward reducing structural unemployment and raising productivity-could lead to much better outcomes.